Fine‐Tuning the Photophysics of Donor‐Acceptor (D‐A3) Thermally Activated Delayed Fluorescence Emitters Using Isomerisation. Issue 2 (15th December 2022) - L. dos Santos, Paloma; de Sa Pereira, Daniel; Eng, Julien; Ward, Jonathan S.; Bryce, Martin R.; Penfold, Thomas J.; Monkman, Andrew P.
Abstract: Here two D–A3 regioisomers, comprising three dibenzothiophene‐ S, S ‐dioxide acceptor units attached to a central triazatruxene core, are studied. Both molecules show thermally activated delayed fluorescence (TADF), however, the efficiency of the TADF mechanism is strongly affected by the D–A substitution position. The meta ‐ substituted emitter (1 b ) shows a slightly higher‐lying singlet charge transfer state and a lower‐lying triplet state than that observed in the para ‐ substituted emitter (1 a ), resulting in a larger singlet–triplet splitting (Δ E ST ) of 0.28 eV compared to only 0.01 eV found in 1 a . As expected, this Δ E ST difference strongly impacts the reverse intersystem crossing (rISC) rates and the para‐ isomer 1 a exhibits a much faster delayed fluorescence emission. Calculations show that the triplet energy difference between the two isomers is due to steric hindrance variances along the donor–acceptor rotation axis in these molecules: as 1 b is less restricted, rotation of its acceptor unit leads to a lower T1 energy, further away from the region of high density of states (the region where larger vibronic coupling is found, favouring rISC). Therefore, our results show how the substitution pattern has a marked effect on triplet state energies and character, verifying the key structural designs for highly efficient TADF materials. Abstract : Substitution pattern has a marked effect on triplet state energies and character, verifying the key structural designs for highly efficient thermally activateddelayed fluorescence (TADF) materials. 1 a and 1 b show TADF, however, the efficiency of the TADF mechanism is strongly affected by the donor – acceptor (D–A) substitution position. Meta ‐substituted 1 b has a lower‐lying triplet state than that observed in the para ‐substituted 1 a, resulting in a larger singlet–triplet splitting (Δ E ST ) of 0.28 eV compared to only 0.01 eV found in 1 a . As expected, these differences strongly impact the lifetime of delayed fluorescence emission.